[Recenzja]: Ireneusz Ihnatowicz, Vademecum do badań nad historią XIX i XX wieku. T. 1. Warszawa 1967, ss. 187; T. 2. Warszawa 1971, ss. 233. Państwowe Wydawnictwo Naukowe - Kumor, Bolesław (Archiwa, Biblioteki i Muzea Kościelne, 1972)
-